SUSTAINABLE USE OF RECYCLED AGGREGATE IN CONCRETE - Mr. Dupargude Naveenkumar R.; Mr. Patole Nikhil G; Mr. Rathod Shubham L.; Mr. Swami Nityanand P; Prof. Miss. Mamdyal Kalyani (International Journal of Innovations in Engineering Research and Technology, 2023)
The research work carried out here primarily deals with use of recycled aggregates in concrete to achieve sustainability. Slump, percentage of RCA, compressive strength and split tensile strength are among the various parameters observed during the research. Result obtained by theoretical formulation has been validated first by comparing the concrete cubes casted and cured. For M25 grade, replacement of 75% RCA shows 11.89% cost reduction for 1m3 concrete. For M30 grade, replacement of 75% RCA shows 7.12% cost reduction for 1m3 concrete.